PERBEDAAN HASIL BELAJAR EKONOMI SISWA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) DAN NUMBERED HEADS TOGETHER (NHT)DI KELAS XI IPS SMA S PONDOK PESANTREN DR. MOHAMMAD NATSIR KECAMATAN LEMBAH GUMANTI KABUPATEN SOLOK - Sri Yani, Dewi; Akhirmen, Akhirmen; Yulna, Dewita (Pendidikan Ekonomi, 2014)
Â ABSTRACTÂ This research has a background by result learn test economics of mid semester of I class student of XI IPS SMA S Maisonette of Pesantren DR. Mohammad Natsir School Year 2013 / 2014 still lower under Complete Criterion Minimize ( KKM). Process study which tend to centrally at student and teacher less accustomed to train its ability in comprehending xself items Iesson of economics. This research aim to to know difference of result learn student economics using model study of type co-operative of Teams Games Tournament ( TGT) and of Numbered Heads Together ( NHT) in class of XI IPS SMA S Maisonette of Pesantren DR. Mohammad Natsir. Pursuant to result of data analysis obtained by experiment class average value 1 equal to 77,23 and experiment class mean 2 equal to 72,46. For the examination of hypothesis used by test of t constructively SPSS version 15.0, obtained by value of t calculate 2,023 bigger than price of t the tables of 2,000 meaning raised to be hypothesis to be accepted [by] [at] real level = 0,05. Inferential that there are difference of result learn student economics using model study of type co-operative of Teams Games Tournament ( TGT) and of Numbered Heads Together ( NHT) in class of XI IPS SMA S Maisonette of Pesantren DR. Mohammad Natsir, result of learning by using model study of type co-operative of Teams GamesTournament ( Higher TGT) from at result learn by using model study of type co-operative of Numbered Heads Together ( NHT).